THE EFFECT OF INDUSTRIAL WEST WATER ON ENVIRONMENTAL POLLUTION AND LAND DEGRADATION AT BAIJI NITORGEN FERTILIZERS FACTORY - Jasim K. Shallal (Mesopotamia Journal of Agriculture)
Nitrogen fertilizers factory is situated to the west of the river Tigris Kms north of Baiji, it is one of the biggest nitrogen fertilizers companies in Iraq. This factory disposes ( ) /day of industrial waters as average through a Kms channel. The study was conducted near the basin an area about donamas. The soil of this area is a loamy-sand with a content of Ca and Gypsum and poor plant cover. Two experiments were carried out, one was an agricultural field study, the second was carried out in the laboratory. Local barely crop was planted, some of the treatments were irrigated with industrial waste waters and others with Tigris river waters to know the effect of industrial waters on environmental pollution and land degradation by the quantity of and heavy elements washed towards ground water. The results showed that industrial waters caused an increase in leached nitrate level toward groundwater at rate approximately compared with river water treatment, and this quantity of nitrate ( ) is very trace and dose not exceed ( ). However, this quantity may have some effects in the future on the phenomenon of Eutrophication and the infection of children and animals with Methomoglobnemia.